A Cry from the Grave - Woodhead, Leslie (United Kingdom : Antelope ; WNET/Thirteen ; NPS ; WDR - Westdeutscher Rundfunk, 1999)
This detailed account of the massacre of an estimated 8000 Muslim men and boys in July 1995, in Srebrenica, relies on eye witness testimonies and on shocking telltale footage. Combining the testimony of witnesses, interviews with senior investigative and judiciary figures, and previously unseen footage shot by the Serbs and Dutch peacekeeping soldiers, the director tells the story of a brutal 72 hours in the life and death of several thousands of Muslim refugees under the protection of the United Nations’ safe areas. Extracts of the film were shown at the ICTY (International Criminal Tribunal for the Former Yugoslavia) in the Hague as well, at the trial of Bosnian Serb commander, General Radislav Krstić, who, alongside indicted war criminal, General Ratko Mladić, was implicated in the genocide.
Duration: 01:44:00
Keywords: Documentary films